School Physical Education and Gender: Influences from outside the school at participation in classes - Juliana Fagundes Jaco; Sra. Helena Altmann (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
Participation in physical education classes is a complex issue; many factors lead students to participate in classroom activities in different ways. This research examines how the way to take part in the class is influenced by experiences outside of school. In this way, seeks to analyze how the actions and family discourses influence the different interests of girls and boys, such as the participation in physical activities outside of school. Also, examines the influence of the participating inside of the school, and how expectations and understandings of bodily practices for boys and girls influence different ways to participate in classes when comparing the male and female gender. For this, held semi-structured interviews and classroom observations into four groups of the eighth year of two public schools in the city of Campinas-SP. The notes of this research indicated that the experience and knowledge of the body and body practice outside of school have the big influence on the ways of participating in classes. The cultural environment of the students gave different experiences and understandings for boys and girls in the knowledge that circulate in physical education classes and contributed in different ways to participate in class. Keywords: Physical Education, Gender, Participation